The Effectiveness of Using the Suggestopedia Method on the Student’s Narrative Writing Ability at Class X Madrasah Aliyah Nurul Falah Airmolek - Riyanti, Adelia; Novita, Loly; Wahyuningsih, Destri (Pubmedia Jurnal Pendidikan Bahasa Inggris, 2025)
This research aims to investigate the effect of the Suggestopedia method on the narrative writing ability of class X students at Madrasah Aliyah Nurul Falah Airmolek. The study employed a quantitative approach using a quasi-experimental design. Two classes were selected as research samples: class X.1 as the experimental group and class X.2 as the control group, each consisting of 28 students. Both groups were given a pre-test and a post-test to measure their narrative writing ability before and after the treatment. The experimental class was taught using the Suggestopedia method, which incorporates elements such as relaxation, music, positive suggestion, and interactive storytelling. Meanwhile, the control class received conventional teaching without the use of Suggestopedia techniques. Students’ writing performance was assessed based on five aspects: content, organization, grammar, vocabulary, and mechanics. In conclusion, the Suggestopedia method positively and significantly influences students’ writing performance, helping them achieve better outcomes in narrative   writing tasks. Therefore, it is recommended that English teachers adopt this method as an alternative strategy to improve students’ motivation, reduce anxiety, and enhance their narrative writing skills